Analisa Pengaruh Pengaturan Kerja Operator Terhadap Pencapaian Keluaran Produksi - Qomarotun Nurlaila (Jurnal Sistem dan Manajemen Industri, 2017)
PT. XYZ is a manufacturing company that produces the constituent components of HDD (Hard Disk Drive) products. One of the products produced by PT. XYZ made from rubber. The product has a strict specification, both for the accuracy of size and for display. One of the problems faced by PT. XYZ is the output of a 100% unstable check section even though the amount of human resources used is the same every day. There is a variation of the output / clock / operator from 650 to 714.4 pieces. This study aims to analyze the cause of the variation of output / hour / operator and to find solutions to minimize the output variation. The result of this research can be concluded that the cause of variation of output / hour / operator is the number of product type checked by operator not always the same every day. Where more and more types of products are checked then the smaller the output on that day. To get maximum results then the operator only do one type of product every day. If not possible then cultivated to a minimum operator change the type of product checked. It requires expertise from the supervisor to manage the work of the operator in an effort to get the maximum output.